(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2017)
In order to talk about the link between dance and interculturalilty, is necessary to remove the history, identities, cultures, and feelings from the dancers that conform one of the most multicultural folkloric ballet group as Nicaragua Mía is. Through the analysis of interpersonal relations living dancers of this dance group it has been possible to discover the role played family life, companionship and friendship for learning intercultural skills. In other words, what is not seen, and that goes beyond the staging is to have learned about the traditions and customs of the other. In the Nicaragua Mía group converge different identities and different worldviews. But what has allowed this multicultural group become a cultural group has been the active role that each of the dancers and the same dance teacher played as cultural mediators. The ethnographic method allowed us to understand the learning process leading to the group not only to rediscover their culture, but to interpret and translate for others. While opening the possibility to know the roots of the other and evaluate them. Raíces - Revista Nicaragüense de Antropología. Año 1 No. 1/2017: 118-132